Functional genomics of PCOS: from GWAS to molecular mechanisms. (March 2015) - McAllister, Jan M.; Legro, Richard S.; Modi, Bhavi P.; Strauss, Jerome F.
Highlights GWAS have identified FHSR, LHCGR, INSR, and DENND1A as PCOS candidate genes. Overexpression of DENND1A variant 2 increases androgen biosynthesis in theca cells from normal cycling women, converting them to a PCOS phenotype. DENND1A, LHCGR, INSR, and RAB5B form a hierarchal signaling network that can influence androgen synthesis. DENND1A variant 2 is a new diagnostic and therapeutic target for PCOS.